1999
DOI: 10.1104/pp.121.3.929
|View full text |Cite
|
Sign up to set email alerts
|

The t-SNARE AtVAM3p Resides on the Prevacuolar Compartment in Arabidopsis Root Cells

Abstract: Protein cargo is trafficked between the organelles of the endomembrane system inside transport vesicles, a process mediated by integral membrane proteins called SNAREs (soluble N-ethylmaleimide sensitive factor attachment protein receptors) that reside on the surface of the vesicle (v-SNAREs) and target membrane (t-SNAREs). In examining transport of cargo between the trans-Golgi network and the vacuole in Arabidopsis, we have previously characterized AtPEP12p as a t-SNARE residing on the prevacuolar compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…Because each of these gene families contains three paralogous members that show high protein sequence identity, it was possible that the individual members of each family would perform redundant functions. However, prior studies have suggested that this was not the case, because individual members within each group were found to have distinct localizations (Sato et al, 1997;Sanderfoot et al, 1999;Bassham et al, 2000). Consistent with these results, we have found that gene disruptions in single syntaxin genes from these families are lethal to the male gametophyte, indicating that each member of these gene families has a unique essential function.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Because each of these gene families contains three paralogous members that show high protein sequence identity, it was possible that the individual members of each family would perform redundant functions. However, prior studies have suggested that this was not the case, because individual members within each group were found to have distinct localizations (Sato et al, 1997;Sanderfoot et al, 1999;Bassham et al, 2000). Consistent with these results, we have found that gene disruptions in single syntaxin genes from these families are lethal to the male gametophyte, indicating that each member of these gene families has a unique essential function.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that the complementation is not due to overexpression of the transgene; in fact, it appears that the amount of T7-SYP21 protein is much less than the endogenous SYP21 protein. The amount of T7-SYP21 being produced is also less than the amount of SYP22 in these plants (see Sanderfoot et al, 1999). This is Leaf tissue was homogenized, and equivalent amounts of total protein from wild-type (lane 1), SYP21/syp21-1 plants (lane 2), and syp21-1::T7-SYP21 plants (lane 3) were separated by SDS-PAGE and blotted with SYP21 antiserum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Arabidopsis protein was also initially reported to be located on the tonoplast in shoot apical meristems (Sato et al, 1997). However, further examination of the localization of AtVAM3 in different tissues by gradient fractionation and by immunoelectron microscopy using both specific antibodies and epitope tagging demonstrated that in roots and leaves, AtVAM3 is found on the PVC, where it co-localizes with AtPEP12, and is not detectable on the tonoplast (Sanderfoot et al, 1999). AtVAM3 therefore is probably involved in vesicle transport from the transGolgi network to the PVC or in the fusion of prevacuoles, rather than in the transport from the PVC to the vacuole, at least in roots and leaves.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%